Investigating telecollaborative genres: analysis of teletandem oral sessions communicative purpose through learners’ diaries - Rampazzo, Laura (Estudos Linguísticos (São Paulo. 1978), 2021)
This paper aims to investigate the communicative purpose of a telecollaborative genre, namely the initial teletandem oral session (iTOS), the first virtual encounter between learners who participate in the Teletandem Brasil project. Although telecollaborative genres are still underexplored, studies have been advancing in observing the development of a community, and in identifying the patterns of action that are effective. Through the analysis of 17 learners’ diaries, available at Multimodal Teletandem Corpus, the present study examines students’ stance on the communicative purpose of the genre. Results suggest that learners recognize the purpose of iTOS to be to get to know their partners and find common ground, and indicate that both learners and researchers have similar views on what the communicative purpose of the genre iTOS is.